Effects of bullying on symptoms of depression and anxiety, the importance of parental support - Elísa Þorsteinsdóttir 1989- (2014)
Over the years bullying has increased dramatically and a significant number of children are involved in bullying, either as victims or as bullies themselves. Research has found bullying to be associated with self reported symptoms of anxiety and depression among adolescents while parental support is associated with lower levels of depressive and anxiety symptoms among adolescents. The main purpose of the current study was to investigate further the relationship between bullying and symptoms of depression and anxiety and whether this relationship varied dependent on parental support. The relationship between parental support and the frequency of bullying was also investigated. The present study used archival data “Ungt Fólk 2004” (Youth in Iceland 2004) collected by The Icelandic Centre for Social Research and Analysis. Participants in the study were students from 29 high schools in Iceland, 952 boys and 1.012 girls (22 participants did not register their sex). The results showed that bullying was associated with increased symptoms of depression and anxiety among the adolescents while parental support decreased these symptoms. Parental support also reduced bullying. The results also showed that the effects of bullying did not vary dependent on parental support. Key words: Bullying, depression, anxiety, parental support Einelti hefur aukist gífurlega á síðustu árum og mikill fjöldi barna tengist einelti á einhvern hátt, ýmist sem gerendur eða þolendur. Rannsóknir hafa sýnt að einelti tengist bæði þunglyndis- og kvíðaeinkennum á meðal unglinga og að stuðningur foreldra tengist færri þunglyndis- og kvíðaeinkennum á meðal unglinga. Tilgangur rannsóknarinnar var að rannsaka betur sambandið á milli eineltis og þunglyndis- og kvíðaeinkenna og athuga hvort stuðningur foreldra hefði áhrif á þetta samband. Sambandið á milli stuðnings foreldra og tíðni eineltis var einnig skoðað. Rannsóknin notaði fyrirliggjandi gögn, Ungt Fólk 2004, sem fengin voru frá Rannsóknum og Greiningu. Þátttakendur í rannsókninni voru nemendur ...